Industry concentration and the cross-section of stock returns: Evidence from the UK - Hashem, Nawar; Su, Larry (Journal of Business Economics and Management, 2015)
In this paper, we examine the relationship between market structure and ex- pected stock returns in the London Stock Exchange during 1985 and 2010. Using Fama- MacBeth regressions, we find that industry concentration is negatively related to average stock returns, even after controlling for beta, size, book-to-market equity, momentum, and leverage. In addition, there is a strong evidence of a growth effect. Firms or industry portfolios with smaller book-to-market ratios have significantly higher returns. In contrast, beta is never statistically significant. The above results are robust to firm- and industry- level regressions, and the formation of firms into 100 size-beta portfolios. Our findings indicate that competitive industries earn, on average, higher risk-adjusted returns than concentrated industries. An explanation is that investors in more competitive industries require larger premiums for greater distress risks associated with these industries. Our paper is one of the first to link market competition with the average stock returns in the UK, and contributes to the asset pricing literature by extending the evidence from the US to another important financial market.